2003
DOI: 10.1046/j.1350-1925.2003.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic transmission to colonic circular muscle of children with slow‐transit constipation is unimpaired, but transmission via NK2 receptors is lacking

Abstract: Tachykinins (TKs) colocalize with acetylcholine in excitatory motor neurones supplying human colonic circular muscle (CCM). Some children with slow-transit constipation (STC) have reduced TK-immunoreactivity in nerve terminals in CCM suggesting a deficit in neuromuscular transmission. This study aimed to test this possibility. Seromuscular biopsies of transverse colon were obtained laparoscopically from STC children (37, 17 with low density of TK-immunoreactivity). Specimens of transverse (17) and sigmoid colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 37 publications
(63 reference statements)
1
31
0
Order By: Relevance
“…In addition, both a reduction in the density of tachykininimmunoreactive nerve fibres in human colonic circular muscle (Porter et al, 1998) and decreases in tachykininsignalinghavebeen observed in patients with slow transit constipation consistent with tachykinins having apro-kinetic effect. (King et al, 2010;Stanton et al, 2003).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In addition, both a reduction in the density of tachykininimmunoreactive nerve fibres in human colonic circular muscle (Porter et al, 1998) and decreases in tachykininsignalinghavebeen observed in patients with slow transit constipation consistent with tachykinins having apro-kinetic effect. (King et al, 2010;Stanton et al, 2003).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The results of many pharmacological studies have combined to show that TKs-induced contraction via NK2r is reduced in patients affected by constipation, diverticulosis, and inflammatory bowel disease (Al-Saffar and Hellstrom, 2001;Liu et al, 2002;Cao et al, 2004a,b; for reviews, see Lecci et al, 2004Lecci et al, , 2006. Moreover, in colonic circular muscle of children with slow-transit constipation, neuromuscular transmission via NK2r is lacking (Stanton et al, 2003).…”
mentioning
confidence: 96%
“…The NK2r antagonists MEN10376 and GR94800 reduced the tetrodotoxin-sensitive spontaneous motility of the circular muscle layer (Cao et al, 2004b). In the circular muscle layer the NK2r antagonist SR48968 greatly decreases the atropine-sensitive EFS-induced contractions, suggesting that NK2r might be involved in the prejunctional neuronal cholinergic processes modulating colonic motility (Stanton et al, 2003;Maselli et al, 2004). The results of many pharmacological studies have combined to show that TKs-induced contraction via NK2r is reduced in patients affected by constipation, diverticulosis, and inflammatory bowel disease (Al-Saffar and Hellstrom, 2001;Liu et al, 2002;Cao et al, 2004a,b; for reviews, see Lecci et al, 2004Lecci et al, , 2006.…”
mentioning
confidence: 96%
“…There is also evidence that the interval between CMCs is reduced in the transverse colon and splenic flexure (9). Other studies have demonstrated reductions in specific neurochemical classes of myenteric neurons in STC patients (4,15,21,32), in addition to reduced density of pacemaker cells (16) or specific types of neuromuscular transmission (31). Whether anatomical or functional changes in the large intestine of STC patients represents a cause or an effect of STC is not fully clear.…”
mentioning
confidence: 99%